2021
DOI: 10.1253/circj.cj-21-0349
|View full text |Cite
|
Sign up to set email alerts
|

Endotyping in Heart Failure ― Identifying Mechanistically Meaningful Subtypes of Disease ―

Abstract: Endotyping is an emerging concept in which diseases are classified into distinct subtypes based on underlying molecular mechanisms. Heart failure (HF) is a complex clinical syndrome that encompasses multiple endotypes with differential risks of adverse events, and varying responses to treatment. Identifying these distinct endotypes requires molecular-level investigation involving multi-"omics" approaches, including genomics, transcriptomics, proteomics, and metabolomics. The derivation of these HF endotypes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The worldwide public health concern of heart failure (HF) affects around 2% of people in developed countries [ 1 , 2 ], resulting in symptoms associated with insufficient cardiac output [ 2 , 3 ]. The three subtypes of heart failure are HF with reduced left ventricular ejection fraction (HFrEF) EF <40% (amended to ≤ 35%), HF with preserved LVEF (HFpEF) in patients with an EF greater than 50%, LV diastolic dysfunction, and evidence of structural heart disease (HFmrEF) in patients with an LVEF of 40-49%, diastolic dysfunction, increased BNP concentrations, and evidence of structural heart disease [ 4 , 5 ]. The etiology and pathophysiological characteristics of HFpEF are complex and heterogeneous [ 6 , 7 ], and even individuals specializing in HF may have difficulty accurately diagnosing this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide public health concern of heart failure (HF) affects around 2% of people in developed countries [ 1 , 2 ], resulting in symptoms associated with insufficient cardiac output [ 2 , 3 ]. The three subtypes of heart failure are HF with reduced left ventricular ejection fraction (HFrEF) EF <40% (amended to ≤ 35%), HF with preserved LVEF (HFpEF) in patients with an EF greater than 50%, LV diastolic dysfunction, and evidence of structural heart disease (HFmrEF) in patients with an LVEF of 40-49%, diastolic dysfunction, increased BNP concentrations, and evidence of structural heart disease [ 4 , 5 ]. The etiology and pathophysiological characteristics of HFpEF are complex and heterogeneous [ 6 , 7 ], and even individuals specializing in HF may have difficulty accurately diagnosing this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Many sncRNAs have been found to play an important role in the regulation of gene transcription, epigenetics, and posttranslational messenger RNA processing. 6,36 A number of studies have shown that concentrations of circulating sncRNAs can be measured noninvasively in the blood and change in response to an array of acute and chronic disease states. 7,8,[37][38][39] Among sncRNAs, miRNAs are particularly attractive candidates as biomarkers of disease.…”
Section: Results In Contextmentioning
confidence: 99%
“…'Multi-omics' technology is necessary to adequately understand the complex molecular milieu of human diseases. Molecular profiling can classify diseases like HF by analysing the molecular signatures associated with the disease at various omics levels 30,31 (Table 1).…”
Section: Molecular Approachmentioning
confidence: 99%
“…‘Multi‐omics’ technology is necessary to adequately understand the complex molecular milieu of human diseases. Molecular profiling can classify diseases like HF by analysing the molecular signatures associated with the disease at various omics levels 30,31 ( Table 1 ). The integration and deep understanding of these molecular patterns allow for identifying distinct HF pathophysiological changes but also a general perspective of the behaviour of the syndrome ( Figure ) 32 …”
Section: Current Disease Classifications Do Not Encompass the Complex...mentioning
confidence: 99%